Prediction of Paracetamol Solubility in Binary Solvents Using Reichardt’s Polarity Parameter Combined Model - Elaheh Rahimpour; Abolghasem Jouyban (Liquids, 2023)
The objective of this research is to propose a general model utilizing the solvatochromic polarity of electronic transition energy (ET) of the Reichardt indicator to predict paracetamol solubility in the solvent mixtures. In order to model validation, the available ET (30) values of nine aqueous mixtures obtained from existing literature sources were utilized. The trained model yielded a relatively accurate estimation of paracetamol solubility in the investigated systems.